WASTE TO ENERGY (WTE) TO SAVE THE GREEN PLANET - Hossain, Nazmul; Ivanova, T.B (European Scientific Journal, ESJ, 2014)
Global warming, the increase in the temperature of the earth’s neonsurface air, is the greatest challenge the world is confronting with and world grave concern for earth’s all living creations. Every nation, including large & small, wealthy & poor, developed & developing, is under the impact of the ravage. Since 2009 global average surface temperature has been increasing by 0.6°C every year and the acceleration is even being faster gradually. It has been indicated that by the end of 21th century world’s average surface temperature will increase by 2.4-6.4°C, might exceed the earth’s ability to adapt. The potential consequences of global warming will be devastative, such as rising sea level, increased occurrence of severe weather events, changing pattern of diseases, more frequent of wildfire & drought, severe food & water shortage and lose of tropical forests and many species. The effect of global warming is already in earth and having significant & costly consequences on our climate, our health and our environment. Acceleration of earth atmosphere’s greenhouse gas (GHG) which includes CH4, CO2, CO, N2O emitted through fossil fuel combustion and municipal solid waste (MSW) landfill are responsible for this. On the other hand, there are huge shortage of energy in developing countries like Bangladesh, Nepal, Pakistan where energy shortage is hindering the financial growth, investment opportunities and employment creation and increasing social depression, poverty & illiteracy rate. In addition, 1.3 billion of the world population that is about 20% of the total population still out of the electricity supply facilities and an overwhelming of 2.5 billion people that is around 43% of the total population still rely on biomass as their every day’s cooking fuel, causing household air pollution, many diseases, massive escalation of deforestation & global climate changes. Changing pattern of energy, for example, carbon neutral or carbon negative, easy accessible & cheap sources of energy only can confront the challenges the world is facing today with global warming, global climate changes and rapidly growing energy demand. Waste to energy (WTE) as a green & cheap source of energy could be a viable alternative.